Prevalence and behavioral risk factors for STIs/HIV among attendees of the Ministry of Health hospitals in Saudi Arabia - Sanaa M. Filemban; Yasser A. Yasein; Magdy H. H. Abdalla; Raafat Al-Hakeem; Jaffar A. Al-Tawfiq; Ziad A Memish (Journal of Infection in Developing Countries)
Introduction: Sexually transmitted infections (STI) are a major public health, social, and economic problem leading to morbidity, mortality, and stigma. This study was conducted to determine the prevalence of STIs, investigate behavioral risk factors and the relationship between the STIs/HIV and demographic factors. Methodology: A cross-sectional survey was conducted between 2013 and 2014 among attendees of the Ministry of Health hospitals. Results: The total number of participants was 3,994 (2,441 males and 1,553 females), with a mean age of 31.95 ± 9.45 years (range 12 to 77 years). The prevalence of STIs and HIV was 6.2% and 0.05% respectively. The mean age for infected people with STIs was 29.42 ± 7.51, vs. 32.12 ± 9.55 for non infected (p < 0.05). There was no diffference between infected and non infected people regarding gender, occupation and marital status. The prevalence of STIs was more commonly reported among non-Saudi (10.9%). Drug use (OR = 4.74; 95%; CI: 3.47–6.48), intravenous drug use (OR = 4.51; 95% CI: 1.45–13.12), illegal sex (OR = 10.7; 95% CI: 7.62–13.32), sex for money (OR = 6.36; 95% CI: 4.52–8.93), sex for pleasure (OR=9.76; 95% CI: 7.29–13.07) were significantly associated with STIs. Conclusion: The prevalence of STIs including HIV in Saudi Arabia is low compared to other countries in the region and globally.